Evaluation of the Sustainability Criteria of Forest Management in the Municipality Palma Soriano, Santiago De Cuba Province - Castañeda, Mercedes Aguilar; Iglesias, C José Antonio Bravo; Porto, José Ángel Chang; Acosta, Kellys Cecilia Naranjo (Journal of Forests, 2017)
The monitoring of the criteria and indicators carried out in Cuba to a municipal level and management areas are limited to a valuation according to the established methodology, making an inadequate evaluation of the same ones, what does not allow to obtain results on scientific bases that guarantee a correct valuation to define if the Forest Management is sustainable. This work carries out an evaluation of the criteria and indicators in the municipality "Palma Soriano" Santiago de Cuba province. The indicators were valued by means of a scale that allows judging their behavior using the approved and implemented methodology in Cuba. With these valuations there were carried out the graphs of sustainability, as tools to evaluate the performance of the criteria and indicators during 10 years. It concludes that the evaluation of the acting for each criteria was of " weak", "Excellent", "Extremely weak", "Weak" and "Favorable", for the criteria Forest Covering, Health and vitality of the Forest Ecosystems, Contribution of the Forest Ecosystems to the environmental Services, Productive functions of the Forest Ecosystems and Multiple Socio-economic benefits to cover the necessities of the society respectively.